An analysis of the effect of the amendments to the taxation of foreign non-South African employment income - Naidoo, Linton (Department of Commercial Law, 2020)
When South Africa moved from a source based to a residence based system of taxation on 1 March 2001, all South African residents were now being subject to tax on their world-wide income. Residents working outside the Republic were then at risk of being taxed twice on the employment income derived because of South Africa’s residence basis system of taxation. The section 10(1)(o)(ii) of the Income tax Act No. 58 of 1962 (“IT Act”) exemption was the relief mechanism for residents to prevent the possibility of double taxation on the employment income derived from working outside the Republic. As from the 1st of March 2020, Parliament has amended section 10(1)(o)(ii) of the IT Act. The section is amended so that foreign employment income should not be fully exempt in the hands of a resident. Section 10(1)(o)(ii) of the IT Act currently exempts in full, the foreign employment income derived by a resident subject to certain requirements as per the section. The amendment seeks to exempt the first one million rand (R1m) of a residents’ employment income earned outside of the Republic. Foreign employment income in excess of R1m will be taxed in the Republic, applying the normal tax tables for that particular year of assessment. All other requirements of section 10(1)(o)(ii) will not be affected by the amendment, therefore residents will still be required to fulfil the other requirements of the section such as to spend more than 183 and at least 60 continuous full days outside of the Republic rendering employment services during any 12-month period in order to qualify for the exemption. The primary reason for the amendment of section 10(1)(o)(ii) is to prevent situations where employment income is neither taxed in the foreign country nor in South Africa, i.e. double non-taxation, or where foreign taxes are imposed at a significantly reduced rate on employment income derived from working outside the Republic. The amendment of section 10(1)(o)(ii) exemption will negatively affect a resident earning in excess of R1m and working in a tax free or low tax jurisdiction. There are a few alternatives available to affected residents working outside the Republic such as: 1. Seek relief via section 6quat of the IT Act, which is a tax credit on foreign taxes paid. 2. Apply the relevant Articles of a Double Taxation Agreement (“DTA”) between South Africa and a source country in order to seek relief for juridical double taxation. 3. Immigrate and become a non-resident, which will trigger a deemed disposal for capital gains tax purposes in terms of section 9H(2) of the IT Act.